Sosialisasi Model-Model Pembelajaran Inovatif di SDN 3 Lemo 1 Kabupaten Barito Utara - Rahman, Rahman; Helmi, Helmi (Jurusan Pendidikan Ilmu Pengetahuan Sosial, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
This service activity was carried out to answer the challenge of the low application of innovative learning models at SDN 3 Lemo 1, North Barito Regency, which is still dominated by conventional methods. The main objective of this program is to improve teacher competence in understanding and implementing active and contextual learning approaches according to the spirit of the Merdeka Curriculum. The methods used include socialization of innovative learning model theory, training in lesson plan preparation, micro teaching, class simulation, and making teaching media based on local potential. The results of the activity show an increase in teachers' understanding and skills in implementing models such as Problem Based Learning, Discovery Learning, and Project Based Learning. Evaluation through questionnaires and observations revealed that teachers felt more confident, creative, and collaborative in designing learning. This program also succeeded in bringing about a change in the teaching paradigm from teacher-centered to student-centered. Overall, this activity made a real contribution to improving the quality of basic education in remote areas and is recommended to be replicated in other schools with similar characteristics.